Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376163
|View full text |Cite
|
Sign up to set email alerts
|

Does Smartphone Use Drive our Emotions or vice versa? A Causal Analysis

Abstract: In this paper, we demonstrate the existence of a bidirectional causal relationship between smartphone application use and user emotions. In a two-week long in-the-wild study with 30 participants we captured 502,851 instances of smartphone application use in tandem with corresponding emotional data from facial expressions. Our analysis shows that while in most cases application use drives user emotions, multiple application categories exist for which the causal effect is in the opposite direction. Our findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 92 publications
0
54
0
Order By: Relevance
“…An extensive review of psychological research on emotion regulation, the process model of emotion regulation, the classification of emotion-regulation strategies, the health implications of emotion regulation, and areas for future research. Sarsenbayeva, Z., Marini, G., Berkel, N., van Luo, C., Jiang, W., Yang, K., . .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An extensive review of psychological research on emotion regulation, the process model of emotion regulation, the classification of emotion-regulation strategies, the health implications of emotion regulation, and areas for future research. Sarsenbayeva, Z., Marini, G., Berkel, N., van Luo, C., Jiang, W., Yang, K., . .…”
Section: Resultsmentioning
confidence: 99%
“…More recently, studies have examined ER in naturalistic settings using experience-sampling methods (e.g., Brans, Koval, Verduyn, Lim, & Kuppens, 2013), although the emphasis remains on detecting predefined forms of explicit ER rather than discovering the diverse ER tactics that people use in everyday life. Techniques from computing research offer ways to detect and study these everyday activities, such as measuring ER automatically using smartphones equipped with passive sensing apps (e.g., Sarsenbayeva et al, 2020). In principle, such smartphone-based tools are capable of recording multiple time series that represent a person’s physical and social context, their technology use, and some of the changing physiological, behavioral, and experiential components of emotion (Harari et al, 2016).…”
Section: An Interdisciplinary Research Agendamentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, recent research has shown that smartphone usage may influence users' emotional states as well as emotions might define users' smartphone usage [26,36,45]. Researchers also demonstrate that depending on the content of mobile applications and smartphone use behaviour [37], users may experience either positive or negative affect [36] and vice versa [42].…”
Section: Digital Media and Human Emotionsmentioning
confidence: 99%